DIFFERENTIATED LEARNING STRATEGIES TO CREATE A DIVERSE LEARNING SPACE - Agustina, Dwi Wahyu; Suwandayani, Beti Istanti; Rahmawati, Nur Ita (Global Action and Education for Society, 2025)
Heterogeneous classes present their own challenges in the learning process, where differences in abilities, interests, and learning styles of students require special strategies so that the learning process can be optimum. The aim of research is to analyze differentiated learning strategies to create a diverse learning space that can be implemented at SD Muhammadiyah 4 Batu. The research was conducted using a descriptive qualitative method with a case study approach. Data analysis through the stages of data reduction, data presentation, and conclusion drawing. The results show that the implementation of differentiated learning strategies involves five main aspects, namely physical flexibility, diversity of learning methods, use of various learning resources, creation of an inclusive environment, and utilization of technology. This strategy provides flexibility for students to be able to gain learning experiences according to their individual abilities and needs, and supports the creation of a more inclusive and collaborative learning environment. In addition, this strategy is proven to increase learning motivation and strengthen social interaction between learners in the classroom. Hence, differentiated learning is important in optimizing the learning process in heterogeneous classrooms, supporting learners' academic and social development as a whole.